2020
DOI: 10.5194/angeo-38-1191-2020
|View full text |Cite
|
Sign up to set email alerts
|

Observations of precipitation energies during different types of pulsating aurora

Abstract: Abstract. Pulsating aurora (PsA) is a diffuse type of aurora with different structures switching on and off with a period of a few seconds. It is often associated with energetic electron precipitation (>10 keV) resulting in the interaction between magnetospheric electrons and electromagnetic waves in the magnetosphere. Recent studies categorize pulsating aurora into three different types – amorphous pulsating aurora (APA), patchy pulsating aurora (PPA), and patchy aurora (PA) – based on the spatial extent o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 42 publications
5
25
0
Order By: Relevance
“…They are commonly observed in the recovery phase of substorms, with the greatest occurrence rates in the early morning sector (Jones et al, 2011;Bland et al, 2019;Grono and Donovan, 2020). The energetic electron precipitation (EEP) that produces PsA is thought to arise from chorus wave activity, whereby electrons from the radiation belts are scattered into the atmospheric loss cone (Thorne et al, 2010;Kasahara et al, 2018). The precipitating electrons typically have energies up to the order of 10-100 keV, depositing their energy into the upper mesosphere/lower thermosphere region at approximately 70-120 km altitude (Fang et al, 2008;Turunen et al, 2009;Miyoshi et al, 2010;Tesema et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…They are commonly observed in the recovery phase of substorms, with the greatest occurrence rates in the early morning sector (Jones et al, 2011;Bland et al, 2019;Grono and Donovan, 2020). The energetic electron precipitation (EEP) that produces PsA is thought to arise from chorus wave activity, whereby electrons from the radiation belts are scattered into the atmospheric loss cone (Thorne et al, 2010;Kasahara et al, 2018). The precipitating electrons typically have energies up to the order of 10-100 keV, depositing their energy into the upper mesosphere/lower thermosphere region at approximately 70-120 km altitude (Fang et al, 2008;Turunen et al, 2009;Miyoshi et al, 2010;Tesema et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the upper-band chorus waves cause background stable precipitations (Evans et al, 1987). Recent studies (e.g., Grono & Donovan, 2020;Tesema et al, 2020;Yang et al, 2019) indicated the relationship between the precipitating energy and the shape of the pulsating aurora. The recent reviews about the pulsating aurora and diffuse aurora are found in Nishimura et al (2020).…”
mentioning
confidence: 99%
“…This is clearly seen in the EISCAT electron density measurements as a significant ionization below 80 km. Similar local time evolution of hardening precipitation was recently investigated by Tesema et al (2020b) in a more statistical approach including EISCAT and optical data from the same geographical area. However, the cut-off altitude of the model is 80 km, which causes a large discrepancy between the model and the EISCAT electron density below 80 km.…”
Section: Discussionmentioning
confidence: 65%
“…In addition, the third category, patchy aurora (PA), consists of very persistent structure with limited pulsation at the patch edges. The energy of electrons associated with the pulsating aurora types are different (Yang et al, 2019;Tesema et al, 2020b). From a total of 92 PsA events Tesema et al (2020b) compared the D region ionization level obtained by EISCAT radars for different types of PsA and suggested that PPA is the dominant type of aurora affecting the D region atmosphere.…”
mentioning
confidence: 99%